Time is of the essence: unveiling the rapid response of Populus to insect feeding - Pastierovič, Filip; Čepl, Jaroslav; Kalyniukova, Alina; Mogilicherla, Kanakachari; Hradecký, Jaromír; Bláha, Jaromír; Tomášková, Ivana (Frontiers in Forests and Global Change, 2024)
Plant metabolism response to insect herbivores is the central theme of this publication. Genetically uniform individuals of European aspen (Populus tremula) were exposed to recurrent feeding by spongy moths (Lepidoptera) at specific time intervals. Changes in physiology, contents of phenolics and saccharides were quantified over the first hour. The unconventional experiment design, integrating analytical methods, and timeline led to the revealing of unexpected dynamics in plant metabolism. The time interval between herbivory initiation and sample collection revealed a pivotal moment, with induced defense activating strongly after 5 min of chewing resulting in an increase in catechin and procyanidin B1. After 10 min, a shift to a tolerant strategy occurs and induced substance concentrations return to control levels. Delayed physiological response was recorded as the first significant difference in transpiration between affected and nonaffected plants and was found after 10 min. A different strategy in exploitation of saccharides after spongy moths infestation was applied because the pool of selected saccharides was rising in the leaves but decreasing in the roots. Placing our results in the context of existing knowledge highlights the uncertain conceptual basis behind the often rigid and definitive classifications in induced plant defense or tolerance strategy.